2016
DOI: 10.3390/nu8100589
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Attenuates Renal Tubular Injury in a Mouse Model of Type 2 Diabetes

Abstract: Renal tubular injury is a critical factor in the pathogenesis of diabetic nephropathy (DN). Endoplasmic reticulum (ER) stress is involved in diabetic nephropathy. Tauroursodeoxycholic acid (TUDCA) is an effective inhibitor of ER stress. Here, we investigated the role of TUDCA in the progression of tubular injury in DN. For eight weeks, being treated with TUDCA at 250 mg/kg intraperitoneal injection (i.p.) twice a day, diabetic db/db mice had significantly reduced blood glucose, albuminuria and attenuated renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
3
21
1
Order By: Relevance
“…Renal tissues from the mice were fixed for 24 h at 20˚C in 10% neutral formalin, embedded in paraffin, manually sectioned into 4-µm thick tissue sections and stained with hematoxylin and eosin (H&e), periodic acid-Schiff (PaS) and Masson reagent as previously described (19,20). The paraffin-embedded renal tissue sections were analyzed using immunohistochemistry as described in our previous study (19). Briefly, after dewaxing and hydration, the slides were heated in sodium citrate buffer (10 mM; pH 6) for 10 min at 100˚C and incubated with hydrogen peroxide (0.3%) for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal tissues from the mice were fixed for 24 h at 20˚C in 10% neutral formalin, embedded in paraffin, manually sectioned into 4-µm thick tissue sections and stained with hematoxylin and eosin (H&e), periodic acid-Schiff (PaS) and Masson reagent as previously described (19,20). The paraffin-embedded renal tissue sections were analyzed using immunohistochemistry as described in our previous study (19). Briefly, after dewaxing and hydration, the slides were heated in sodium citrate buffer (10 mM; pH 6) for 10 min at 100˚C and incubated with hydrogen peroxide (0.3%) for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues or cells were lysed with riPa buffer (Beyotime institute of Biotechnology) containing protease and phosphatase inhibitor cocktail, and the protein concentration was measured using the bicinchoninic acid protein assay kit (Bio-rad laboratories, inc.). The protein samples (40 µg per lane for tissue; 30 µg per lane for cells) were separated via SdS-PaGe on 10% gels and transferred to PVdF membranes, as described in our previous study (19). after blocking with PBST containing 3% BSa for 1 h at room temperature, the membranes were incubated with the following primary antibodies overnight at 4˚C: i) GRP78 (1:1,000; Cell Signaling Technology, Inc.; cat.…”
Section: Rna Extraction and Reverse Transcription-quantitative (Rt-q)mentioning
confidence: 99%
“…Moreover, it was found that administration of TUDCA at the prediabetic stage resulted in a marked reduction of diabetes incidence in two different mouse models of type1 diabetes (Engin et al 2013). Later, Zhang et al (2016) treated diabetic mice with intraperitoneal TUDCA and noted a significant reduction of blood glucose level with a significant decreased expression of ER stress markers along with decreases in ER stress-associated apoptotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…40 Short-term treatment with TUDCA was also recently shown to protect against folic acid nephropathy in a mouse model of the disease. 43,44 In this study, we hypothesized that TUDCA treatment would prevent the development of proteinuria, albuminuria and renal glomerular and/or tubular injury in a model of salt-sensitive hypertension, the ET B -deficient rat. 43,44 In this study, we hypothesized that TUDCA treatment would prevent the development of proteinuria, albuminuria and renal glomerular and/or tubular injury in a model of salt-sensitive hypertension, the ET B -deficient rat.…”
mentioning
confidence: 99%
“…41 More recent studies report beneficial effects of TUDCA treatment against aldosterone-infused renal injury 42 and diabetic nephropathy. 43,44 In this study, we hypothesized that TUDCA treatment would prevent the development of proteinuria, albuminuria and renal glomerular and/or tubular injury in a model of salt-sensitive hypertension, the ET B -deficient rat. We further examined whether TUDCA treatment would blunt renal apoptosis and inflammation in response to a high salt diet in the ET B -deficient rat model.…”
mentioning
confidence: 99%